Strategies for high-efficiency salt management in solar-driven interfacial evaporation - Jinjing Yang; Jing Zhang; Zhongxing Xu; Lin Ren; Longshi Rao; Junyang Tao; Yifeng Liao; Shudong Yu (Desalination, 2026)

Nature-inspired bicontinuous-topology 3D-printed TPMS solar interfacial evaporator - Yifeng Liao; Yizhe Liu; Lin Ren; Yujun Wei; Zhijian Huang; Jing Zhang; Zhongxin Xu; Jianing Wu; Junyang Tao; Shudong Yu; Shuo Wu (Chemical Engineering Journal, 2026)

Flame-retardant and electromagnetic-interference-shielding silver nanowire/silicon dioxide/aramid nanofiber/sodium alginate lightweight porous composite for wearable sensors - Xinxin Cai; Hui Liu; Wen Li; Jiwen Hu; Xiaobin Li; Shudong Lin (Carbohydrate Polymers, 2026)

Flame-retardant ladder-like polysilsesquioxane composites enabled by dual crosslinking and functional nano-filler integration - Hui Liu; Xinxin Cai; Wen Li; Jiwen Hu; Yuewen Huang; Bin Wang; Shudong Lin (Chemical Engineering Journal, 2025)

A coupled optical–radiometric modeling approach to removing reflection noise in TLS data of urban areas - Li Fang; Tianyu Li; Yanghong Lin; Shudong Zhou; Wei Yao (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

A comprehensive evaluation of lightning location accuracy using a weighted gridding method - Lin Song; Qingda Li; Jun Yang; Qilin Zhang; Jie Li; Shudong Wang; Yuqing Zhong; Zhiren Zhou; Meng Zheng (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Design of high-efficiency carbonic anhydrase mimics with well-defined Zn sites based on salphen organic framework - Lin Li; Wenjie Xu; Mao Wang; Shuang Li; Shudong Sun; Chong Cheng; Changsheng Zhao (Chemical Engineering Journal, 2024)

Flexible sensor based on conformable, sticky, transparent elastomers for electronic skin - Xinxin Cai; Xinqi Wang; Fuping Bian; Jiayi Li; Ruixiang Zhou; Jiwen Hu; Shudong Lin (Chemical Engineering Journal, 2024)

The mechanism of using magnetized-ionized water in combination with organic fertilizer to enhance soil health and cotton yield - Shudong Lin; Quanjiu Wang; Mingjiang Deng; Kai Wei; Yan Sun; Wanghai Tao (Science of The Total Environment, 2024)

A bioinspired regenerative antimicrobial hydrogel coating for cardiovascular implantable electronic devices - Xudong Yao; Miner Hu; Xinrang Zhai; Junxin Lin; Xiaojun Xia; Wei Wei; Shudong Xia (Chemical Engineering Journal, 2024)

Occurrence and spatiotemporal distribution of natural and synthetic steroid hormones in soil, water, and sediment systems in suburban agricultural area of Guangzhou City, China - Hang Lin; Liangzhuo Zhou; Shudong Lu; Han Yang; Yongtao Li; Xingjian Yang (Journal of Hazardous Materials, 2024)

Enhancing pakchoi (Brassica chinensis L.) agriculture with magnetized-ionized brackish water and organic fertilizers: A sustainable approach to soil quality and crop yield optimization - Shudong Lin; Quanjiu Wang; Kai Wei; Yan Sun; Fanfan Shao; Qingyuan Lei; Mingjiang Deng (Journal of Cleaner Production, 2024)

Assessing the influence of water fertilizer, and climate factors on seed cotton yield under mulched drip irrigation in Xinjiang Agricultural Regions - Shudong Lin; Quanjiu Wang; Mingjiang Deng; Lijun Su; Kai Wei; Yi Guo; Jihong Zhang (European Journal of Agronomy, 2024)

Identification and prediction of climate factors based on factor analysis and a grey prediction model in China - Shudong Lin; Kai Wei; Qingyuan Lei; Fanfan Shao; Quanjiu Wang; Mingjiang Deng; Lijun Su (Environmental Monitoring and Assessment, 2023)

Synergistic effects of biochar and carboxymethyl cellulose sodium (CMC) applications on improving water retention and aggregate stability in desert soils - Fanfan Shao; Senlin Zeng; Quanjiu Wang; Wanghai Tao; Junhu Wu; Lijun Su; Haokui Yan; Yibo Zhang; Shudong Lin (Journal of Environmental Management, 2023)

Influence of ionized saline water on soil water and salt transport in saline soils - Kai Wei; Shudong Lin; Jihong Zhang; Quanjiu Wang; Yi Guo; Weiyi Mu (Irrigation and Drainage, 2023)
The utilization of saline water plays an important role in agricultural production in saline areas to overcome freshwater shortages. Ionized saline water might alleviate the adverse effects of salinity on soil and plants. In this study, field experiments were conducted to study the effect of ionized saline water on the soil water content and salinity distribution in a sandy soil under a surface emitter. Passing groundwater through an ionization system installed on a feeding pipeline resulted in producing ionized saline water. Three emitter discharges (1.0, 1.8, 3.1 L h −1 ) and two water types (non‐ionized and ionized saline water) were considered in the experiments. As a result of using ionized saline water, soil water content and salt leaching increased. Ionized treatment increased the salinity desalination rate by 31, 33 and 26% for surface soil layer in comparison with non‐ionized treatments of 1.0, 1.8 and 3.1 L h −1 , respectively. It was found that using ionized saline water could decrease the surface wetting radius by 6–9% and increase the wetting depth by 11–17%. A discharge rate of 1.8 L h −1 was recommended as the optimal discharge rate for ionized saline water under drip irrigation. The results indicated that saline water could be improved through ionized treatment for agricultural irrigation in saline soils in an arid region.

Combined effects of the earthworm casts application and fallow time on runoff and sediment loss by raindrop splashing in the Loess Plateau, China - Fanfan Shao; Wanghai Tao; Junhu Wu; Shudong Lin; Quanjiu Wang (Journal of Environmental Management, 2023)

Experimental Study on Ultra-low Friction Effect of Granite Block Under Coupled Static and Dynamic Loads - Dongqiao Liu; Youwen Lin; Yang Wang; Manchao He; Shudong Zhang (Geotechnical and Geological Engineering, 2020)